Almost forgotten experiential knowledge of de-escalation - Behrendes, Udo (Public Order Policing, 2024)
In the mid-1980s, a group of experts concluded that those who policed assemblies did not consistently integrate past operational experience in current operational planning, thus those experiences were continually lost and needed to be acquired anew. This includes assessments of the psychological impacts of police tactics on assembly participants and the larger public. Evidence suggests that contemporary experts would discover similar findings. This chapter examines examples of (historic) police approaches that eased tensions in conflict situations at assemblies. The authors identify related de-escalation tactics and training supported by scientific evidence.